Some Considerations on Serious Road Traffic Injuries - Holló, P.; Kiss, D. (Acta Technica Jaurinensis, 2014)
In the EU in 2011 the number of the victims of serious road injuries was more than 250,000 and the death tolls were 28,000. In the last period (between 2001 and 2011) the number of those who lost their lives as a result of road accident decreased ordinarily by 43 percent in the EU countries on average, whereas that of the seriously injured by 36 percent – in the light of these countries’ own definitions differing from one another. The MAIS3+ is the adopted common EU definition, that is all 3-grade or above values according to the Maximum Abbreviated Injury Scale (MAIS). Although the definition seems professionally justified, in our view further clarification is necessary. For the years 2014 and 2015 the EU has already drawn up specific tasks for the member states. Since the Baltic States were particularly successful in the field of road safety in the last 10 years, it is certain that in the future they can do a lot in order to have the number of serious road accident victims significantly reduced and also internationally compared and assessed.